Penerapan teknologi mesin pengering limbah kulit udang untuk produksi pakan ternak: pendekatan sirkular ekonomi untuk pemberdayaan nelayan dan keberlanjutan lingkungan di UD Cahaya Bersama, Kelurahan Nelayan Indah - Puspita, Riana; Reakha Zulvatricia; Banjarnahor, Marali (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2025)
The application of technology in waste management, particularly shrimp shell waste, has become a key focus in supporting environmental sustainability and community empowerment, especially in coastal areas. One promising initiative is the utilization of shrimp shell waste as a raw material for animal feed production. According to statistical data, the fisheries waste in Indonesia, particularly from the shrimp processing industry, amounts to approximately 200,000 tons annually, with 35% of it derived from shrimp shell waste. This study aims to explore the utilization of shrimp shell waste in animal feed production through the development of a drying machine technology designed to process this waste efficiently. The novelty of this research lies in the integration of shrimp shell drying technology within the context of coastal community empowerment, utilizing a circular economy approach that promotes environmental sustainability and enhances community welfare. The methodology includes stages of planning, preparation, analysis, implementation, as well as mentoring and evaluation. The results of this community service indicate that this technology successfully increased the partners' knowledge on processing shrimp shell waste into nutritious animal feed and boosted their income by up to 20%. Thus, the shrimp shell drying machine technology contributes not only to reducing marine pollution but also provides a sustainable economic solution for coastal communities.